The influence of street furniture, tree trunks, and traffic in urban scenarios on ray tracing simulations in the millimeter wave band. Issue 4 (18th March 2016) - Göktepe, Bariş; Peter, Michael; Weiler, Richard J.; Keusgen, Wilhelm
Abstract : In this paper, the influence of tree trunks, cylindrical street furniture such as lamp posts, and traffic on ray tracing simulations in an urban scenario is analyzed. Tree trunks and lamp posts are modeled by cylinders and propagation characteristics computed according to the Uniform Theory of Diffraction. The influence of traffic is analyzed by simulations with moving vehicles. In order to get an understanding of the spatial characteristics of the channel, simulations with static and also mobile receivers have been performed, in line with a measurement campaign in the same environment. The simulation results show a good agreement with the measurements.